2018
DOI: 10.1016/j.jpsychores.2018.03.003
|View full text |Cite
|
Sign up to set email alerts
|

The association between depression and eating styles in four European countries: The MooDFOOD prevention study

Abstract: Our results suggest that depression is related to more unhealthy eating styles. Diminishing unhealthy eating styles in subthreshold depressed persons could potentially reduce adverse health consequences like weight gain, unhealthy dietary patterns and weight-related diseases. It is also possible that interventions that decrease depressive symptoms can lead to a decrease in unhealthy eating styles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 67 publications
5
32
0
3
Order By: Relevance
“…Several studies have shown that measures of uncontrolled eating positively correlate with Neuroticism (Elfhag & Morey, 2008;Provencher et al, 2008), a measure of sensitivity to negative emotions. The same measures also correlate positively with depressive symptoms (Konttinen et al, 2014;Paans et al, 2018).…”
Section: Longitudinal Associations Between Food Intake and Uncontrollmentioning
confidence: 80%
“…Several studies have shown that measures of uncontrolled eating positively correlate with Neuroticism (Elfhag & Morey, 2008;Provencher et al, 2008), a measure of sensitivity to negative emotions. The same measures also correlate positively with depressive symptoms (Konttinen et al, 2014;Paans et al, 2018).…”
Section: Longitudinal Associations Between Food Intake and Uncontrollmentioning
confidence: 80%
“…Several studies have shown that measures of uncontrolled eating positively correlate with Neuroticism (Elfhag & Morey, ; Provencher et al ., ), a measure of sensitivity to negative emotions. The same measures also correlate positively with depressive symptoms (Konttinen et al ., ; Paans et al ., ).…”
Section: The Three Psychological Constructs Of Uncontrolled Eating: Rmentioning
confidence: 97%
“…The scale presents acceptable psychometric properties [ 48 , 49 ]. In accordance with previous studies [ 39 , 40 ], individual symptoms were categorized into symptoms clusters: mood cluster (16 item ranged from 0 to 30); cognitive cluster (4 items ranged from 0 to 12); and somatic/vegetative cluster (ranged from 0 to 48). See Supplementary Table S1 .…”
Section: Methodsmentioning
confidence: 88%
“…In addition, depressive symptom patterns/clusters have not yet been studied. Previous works proposed to differentiate three symptom clusters [ 40 , 41 ]: mood symptoms (e.g., feeling sad, anxious, reduced pleasure or interest), cognitive symptoms (e.g., concentration difficulties, pessimism, suicidal thoughts), and somatic/vegetative symptoms (e.g., sleeping problems, appetite increase/decrease, aches and pains).…”
Section: Introductionmentioning
confidence: 99%